Stories Of Improvement Of Quality Of City Life: Architectural Aspects - et. al., Zhaina Zhanaykyzy Tolegen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article on the example of the megalopolis of Kazakhstan - Almaty investigates architectural aspects of improvement of quality of city life. Means and the receptions of architectural composition used in the solution of the tasks directed to improvement of quality of life of people in the urban environment make a main objective of this research. Special attention is paid to questions, compliances and devices of architectural space to existing and whenever possible to future, to living conditions of citizens. And also, the flexibility of the layout of the architectural space to unforeseen changes and a lively and mutual connection with the real reality. The authors of the article make a conceptual proposal to improve the quality of the spatial environment of social housing. These are spatial modules, with the possibility of various compositional arrangements. The importance of the role of architects and designers in improving the quality of life of urban residents in various urban settings is confirmed./The article analyzes public buildings that serve as city attractions, public and residential spaces, urban infrastructure, landscape and their role in improving the quality of life of citizens. Key conclusion of a research is confirmation of a role of architects as moderators of people behavior in space. The worldview and professional training of an architect is a driving force in solving the problem of improving the quality of life in an urban environment.